2016
DOI: 10.3109/07435800.2015.1124437
|View full text |Cite
|
Sign up to set email alerts
|

Sex effect on insulin secretion and mitochondrial function in pancreatic beta cells of elderly Wistar rats

Abstract: This study demonstrates a sex dimorphism in the age-associated impairment of pancreatic beta cell function in elderly rats, while the potential mechanism may be related to the sexual differences in mitochondrial biogenesis and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
6
27
0
Order By: Relevance
“…Moreover, insulin secretion capacity associated with mitochondrial function declines with aging which is a contributing factor to T2D. Evidence showed that elderly male Wistar rats show more significantly decreased mitochondrial function and insulin secretion than elderly females [23], consistent with our results that two mitochondrial function related genes, Cox4i1 and Ndufb7, were identified as downregulated male dependent T2D altered genes.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, insulin secretion capacity associated with mitochondrial function declines with aging which is a contributing factor to T2D. Evidence showed that elderly male Wistar rats show more significantly decreased mitochondrial function and insulin secretion than elderly females [23], consistent with our results that two mitochondrial function related genes, Cox4i1 and Ndufb7, were identified as downregulated male dependent T2D altered genes.…”
Section: Resultssupporting
confidence: 91%
“…In the obese male group (M+HFD), we observed increased insulin and HOMA-IR levels compared with the female obese group, which was in line with another study. 41 In addition, it was shown in another study that insulin resistance is higher among patients with asthma, in line with our results. 42 However, sensitization with OVA after diet-induced obesity caused increased insulin and HOMA-IR levels in the female group when compared with the male group.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, although male and female mammals exhibit the same overall mechanism of nutrient-induced insulin secretion, the fine-tuning of insulin secretion is regulated in a sex-specific manner by sex hormones. GSIS in rodents declines significantly with age in both sexes [27] , [28] . However, isolated islets from female rats at 18 months of age still show higher glucose-stimulated insulin secretion (GSIS) ex vivo than those of males [27] , confirming results obtained in humans [18] .…”
Section: Sex Differences In β-Cell Function Under Normal and Stress Cmentioning
confidence: 98%
“…GSIS in rodents declines significantly with age in both sexes [27] , [28] . However, isolated islets from female rats at 18 months of age still show higher glucose-stimulated insulin secretion (GSIS) ex vivo than those of males [27] , confirming results obtained in humans [18] . Islets from elderly female rats showed elevated mitochondrial function (ATP content and oxygen consumption) compared with males when exposed to high glucose ex vivo .…”
Section: Sex Differences In β-Cell Function Under Normal and Stress Cmentioning
confidence: 98%